Gilbert Keith Chesterton - Ward, Maisie, (Rowman & Littlefield Publishers, 2005)
Maisie Ward's biography of Gilbert Keith Chesterton has long been a cornerstone in Chesterton studies, as well as in the publishing house she and her husband, Frank Sheed, founded in 1926. Originally published in 1942, just six years after Chesterton's untimely death, this book combines Ward's unique perspective as the author's friend and publisher with an examination of his personal correspondence and interviews with his closest friends and family. Here are Chesterton's childhood and school days, the friendship and foolery of youth, his early theological development, high spirited love letters, the variety and richness of his travel and life abroad, his lectures, his writings, and his indominable spirit. A Sheed & Ward Classic, this re-release of Ward's definitive biography is sure to delight existing "Chestertonians" and introduce a new generation to one of Catholicism's brightest lights. From the new introduction by Andrew Greeley: "This book had a decisive impact on me and on my life when I read it at the age of sixteen—and not merely because my fictional detective Blackie Ryan is an American cousin of GKC's Father Brown. Ms. Ward's biography introduced me not only to a world of literature of which I had been unaware, but to a perspective on literature and life which was enormously attractive because it confirmed many of the insights, instincts, inclinations, biases, and loves which were knocking around in my adolescent skull. I have been a Chestertonian all my life in part because I had been one without knowing it even before I read Ms. Ward's biography."